Decolorization of reactive blue using white rot fungi biomass: optimization, isotherm and kinetic study - Mustafa, Monawa rMunjit; Jamal, Parveen; Al-Khatib, Ma'an Fahmi Rashid (2015)
The textile and dye industries are considered to pose a large threat to the environment. White rot fungi show a great potential in decolorizing Azo dyes. Hence, the present study will investigate the decolorization of Reactive Blue 19, by biosorption using biomass of Panus tigrinus. The process parameters that were varied were: initial concentration, time and pH. The strain showed maximum decolorization of (83.18%) at a pH of 2, contact time of 90 minutes and an initial concentration of 50 mg/l. The equilibrium data was analyzed using Langmuir and Freundlich isotherm. The Langmuir isotherm with a correlation coefficient of 0.932 best describes the uptake of the reactive blue 19 dye, which indicates a homogeneous distribution of active sites on the biomass surface. The kinetic data was analyzed and the results obtained from the kinetic study indicated that the dye uptake process followed the pseudo second-order rate expression, with a correlation coefficient of 0.963, which suggested that chemisorption is the rate-limiting step which controlled the biosorption process.